(untitled) (Journal of the Association for the Study of Australian Literature, 2009)
This paper considers the situation of the changing global market for Australian literary fiction. In particular it uses the case of Gerld Murnane to examine ways in which these changes might be beneficial to at least some authors as we enter an era of ’post-national’ literary fiction. The paper traces the international reception of Murnane’s fiction and the subsequently the development of his global reputation. It incorporates Murnane’s own observations (drawn from personal correspondence with the author) and suggests that although it has been argued that the impacts of globalisation will be detrimental for Australian literary fiction, there may also be some reasons for optimism.